Effect of the angles of the cracks of corroded plate in bonded composite repair (Fracture and Structural Integrity, 2018)
In this study a three-dimensional finite element method analysis of repairing plate with bonded composite patch subjected to tensile load was presented. The effect of the corrosion on the damage of the adhesive (FM73) in the length of inclined crack is presented. The obtained results show that the increase of (DR) is due to the increase of the inclination of the crack against it leads to the decrease of the values of the stress intensity factor in mode I (KI).
Keywords: Composite repair; Corrosion; Damage ratio; Finite element method (FEM); Stress intensity factor in mode I and mode II (KI, KII)